Psikologi Kognitif dalam Pembelajaran Matematika Modern untuk Mengatasi Math Anxiety dan Meningkatkan Kreativitas Numerik Generasi Digital - Adji Seputro; Ahmad Dwi Nurdiyanto (CV. Aksara Global Akademia, 2023)
Mathematics anxiety has long been recognized as a barrier to student achievement, particularly in an era where digital technologies are reshaping education. This study aims to investigate the role of cognitive psychology in modern mathematics learning as a means of reducing math anxiety and enhancing numerical creativity among digital generation learners. Employing an experimental classroom design informed by neuroeducation principles, the research explored how interventions rooted in cognitive regulation, emotional control, and cognitive load management influence student outcomes. Data were collected through pre-test and post-test instruments measuring levels of math anxiety and creativity in numerical problem-solving. The findings demonstrate a significant reduction in mathematics anxiety following the implementation of the neuroeducation-based intervention. Simultaneously, students exhibited marked improvements in creative approaches to numerical challenges, indicating that addressing psychological factors is essential to unlocking mathematical potential. These results highlight the importance of integrating cognitive psychology into mathematics instruction, moving beyond procedural learning toward a holistic approach that considers students’ emotional and cognitive states. The implications extend to educators, curriculum designers, and policymakers, suggesting that modern mathematics education should balance cognitive development, emotional well-being, and creative problem-solving skills to prepare students for the challenges of a rapidly evolving digital world.